Stapecolis, new genus of Ochlerini (Hemiptera: Pentatomidae: Discocephalinae) - Garbelotto, Thereza De A.; Campos, Luiz A.; Grazia, Jocelia (Zootaxa, 2016)
A cladistic analysis of the Herrichela clade (Ochlerini) was conducted to solve problems concerning the systematics of the genus Alitocoris Sailer; this recovered monophyletic groups which are considered to be new genera. Stapecolis gen. nov. is here proposed for two species (S. latus sp. nov. and S. bimaculatus sp. nov.) representing one of those monophyletic groups. The new genus is supported by ten synapomorphies, five of them pertaining to the morphology of the pygophore have not been found together in any other genera of Ochlerini. The female genitalia also has characteristics different from closely related genera.